Optimalisasi Pemeliharaan, Pengujian, dan Penggantian Current Transformer Jenis OSKF-170 - Tria Kasnalestari; Gde KM Atmajaya; Syamsyarief Baqaruzi (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2022)
The electric power distribution system on the transmission line side is carried out at the substati on, which contains several bays. However, containing the primary equipment discussed in this study regarding the Current Transformer (CT) of the CT OSKF-170 type, so that the electric power distribution system can be carried out optimally. The research location is substation area (GI), where the maintenance side is optimised and tested to prevent extensive damage to the substation's electric power distribution. If the CT has damage or disturbances such as current leakage that create inefficient power distribution losses, it can be replaced. Thus, this study examined the results of the insulation resistance measurement of more than 1000 G and on the secondary side the results were 100-500 MΩ. Then, the value of grounding resistance in the R, S, and T phases was less than 1Ω, the tan delta test yielded a measurement value of less than 1 percent, and the turns ratio in the transformer corresponds to the ratio value on the CT OSKF-170 nameplate. The outcomes of the tests were satisfactory in accordance with the criteria for CT maintenance standards.